Exploring Halal Science Literacy in Society: Are People Ready to Choose Halal Products Smartly? - Cintiati, Seni; Afifah, Syifa Nur; Muthmainnah, Ulfah Nurul; Hodijah, Yani Nurul (Perhimpunan Intelektual Muslim Indonesia, 2025)
Consuming halal products is increasingly important for Muslims. However, there are still many people who do not fully understand the concept of halal, so they have the potential to choose products that are not in accordance with Islamic law. This shows the need to increase halal science literacy in society. This research aims to analyze the community's halal science literacy level and identify factors that influence the community's halal science literacy. This research uses quantitative and qualitative methods. The results of the research show that out of 30 respondents representing each of the Garut, Bandung and Tasikmalaya regions, it shows that the community's halal science literacy level is still relatively low, as indicated by the descriptive results, the average attitude aspect is still worth 21.20. Then the researchers also reviewed the relationship between four indicators of halal scientific literacy, namely aspects of knowledge, context, process and attitude, in the correlation statistical results showing a significance value of <0.05. Factors that influence people's halal scientific literacy include: level of education, religious knowledge and access to information obtained. Based on the research results, several strategies that can be implemented to increase public halal science literacy are increasing education and outreach about halal science to the public as well as access to information about halal science to the public. These programs need to touch on the four aspects studied, namely knowledge, context, process and attitude, in order to achieve optimal effectiveness. Increasing halal science literacy is very important to help people choose halal products intelligently and in accordance with Islamic law